Prevalence of alcohol use disorders in individuals with borderline personality disorder: a meta-analysis and meta-regression study - Silva, Stefani Gonzalez; Pedro, Maria Olivia Pozzolo; Castaldelli-Maia, Joao Mauricio (São Paulo Medical Journal, 2026)
BACKGROUND: This review examined the prevalence rate of alcohol use disorders (AUDs)–including heavy episodic drinking, heavy drinking, alcohol abuse, and alcohol dependence–among individuals with borderline personality disorder (BPD). OBJECTIVES: The primary objective of this meta-analysis and meta-regression study was to investigate the prevalence AUDs associated with BPD. DESIGN AND SETTING: We searched PubMed, Google Scholar, Virtual Health Library (VHL/BVS), SciELO, LILACS, EMBASE, and PsycINFO for studies, reports, or abstracts published without language restrictions. METHODS: We searched for reports published from database inception through March 2024. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-analysis Of Observational Studies in Epidemiology guidelines (MOOSE). Based on the extracted data, we performed meta-analyses and meta-regressions. RESULTS: The final sample included 15 articles with 15,603 individuals aged 18 years or older with BPD. The prevalence of AUDs with BPD was 55.28%, while the prevalence of alcohol dependence (AD) was 44.59%, and alcohol abuse (AA) was 18.84%. CONCLUSION: Our findings indicate a high prevalence of AUDs among individuals with BPD, underscoring the need for targeted prevention and treatment strategies. Integrated dual-diagnosis approaches addressing both disorders simultaneously are crucial for improving outcomes. This high prevalence has important implications for public health.